PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN PEMBAGIAN DIVIDEN TERHADAP NILAI PASAR SAHAM PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 PERIODE 2019-2024 (Studi Kasus Perusahaan Tbk. Yang Konsisten Dalam Daftar Indeks LQ45 Selama Periode 2019-2024) - Muhamad Rijik; Agus Supriatna (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. Investment and financial management are fundamental foundations for achieving financial well-being. A sound understanding of investment enables individuals to manage their finances wisely. Stock price movements are influenced by a company’s fundamental conditions, and investors can understand the direction of these movements through fundamental analysis. This analysis is conducted by utilizing data contained in financial statements. One method of financial statement analysis is the use of financial ratios, including Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend per Share (DPS). The research problem and objective of this study are to analyze the effect of ROE, DER, and DPS on stock prices of LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, both partially and simultaneously. This study is a quantitative research using secondary data, with a sample of 25 companies. The data analysis technique employed is panel data regression analysis using the fixed effect model. The results indicate that simultaneously ROE, DER, and DPS have a significant effect on stock prices, with an F-statistic value of 45.14212 and a probability of 0.000000 (< 0.05). Partially, DER has a t-statistic value of 78.72876 with a probability of 0.8369, indicating that DER does not have a significant effect on stock prices. Meanwhile, ROE, with a t-statistic value of 3.691637 and a probability of 0.0001 (< 0.05), and DPS, with a t-statistic value of 1.115248 and a probability of 0.0001, are concluded to have a significant effect on stock prices. Keywords: Return on Equity (ROE), Debt to Equity Ratio (DER), Dividend per Share (DPS), Stock Price, LQ45 Index.